In vivo protein complementation demonstrates presynaptic α-synuclein oligomerization and age-dependent accumulation of 8-16-mer oligomer species - Kiechle, Martin; von Einem, Bjoern; Höfs, Lennart; Voehringer, Patrizia; Grozdanov, Veselin; Markx, Daniel; Parlato, Rosanna; Wiesner, Diana; Mayer, Benjamin; Sakk, Olena; Baumann, Bernd; Lukassen, Soeren; et al. (Cell reports, 2019)
Intracellular accumulation of α-synuclein (α-syn) and formation of Lewy bodies are neuropathological characteristics of Parkinson’s disease (PD) and related α-synucleinopathies. Oligomerization and spreading of α-syn from neuron to neuron have been suggested as key events contributing to the progression of PD. To directly visualize and characterize α-syn oligomerization and spreading in vivo, we generated two independent conditional transgenic mouse models based on α-syn protein complementation assays using neuron-specifically expressed split Gaussia luciferase or split Venus yellow fluorescent protein (YFP). These transgenic mice allow direct assessment of the quantity and subcellular distribution of α-syn oligomers in vivo. Using these mouse models, we demonstrate an age-dependent accumulation of a specific subtype of α-syn oligomers. We provide in vivo evidence that, although α-syn is found throughout neurons, α-syn oligomerization takes place at the presynapse. Furthermore, our mouse models provide strong evidence for a transsynaptic cell-to-cell transfer of de novo generated α-syn oligomers in vivo.